2003
DOI: 10.1007/s00442-003-1348-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO 2 reduces sap flux in mature deciduous forest trees

Abstract: We enriched in CO2 the canopy of 14 broad-leaved trees in a species-rich, ca. 30-m-tall forest in NW Switzerland to test whether elevated CO2 reduces water use in mature forest trees. Measurements of sap flux density (JS) were made prior to CO2 enrichment (summer 2000) and throughout the first whole growing season of CO2 exposure (2001) using the constant heat-flow technique. The short-term responses of sap flux to brief (1.5-3 h) interruptions of CO2 enrichment were also examined. There were no significant a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 48 publications
6
53
3
Order By: Relevance
“…O 3 treatment) did not significantly reduce the CO 2 -driven stimulation in photosynthesis (Uddling et al 2009). Although previous measurements revealed reduced sapflow in our CO 2 -enriched trees (Cech et al 2003;Leuzinger and Körner 2007), we did not measure reduced g s under elevated CO 2 . However, the relationship between A growth and g s suggests improved water-use-efficiency (Fig.…”
Section: Leaf Gas Exchangecontrasting
confidence: 44%
“…O 3 treatment) did not significantly reduce the CO 2 -driven stimulation in photosynthesis (Uddling et al 2009). Although previous measurements revealed reduced sapflow in our CO 2 -enriched trees (Cech et al 2003;Leuzinger and Körner 2007), we did not measure reduced g s under elevated CO 2 . However, the relationship between A growth and g s suggests improved water-use-efficiency (Fig.…”
Section: Leaf Gas Exchangecontrasting
confidence: 44%
“…The average sap flow density measured for ivy (volume of water per unit area per second, 1.5 9 10 -4 m 3 m -2 s -1 ) was higher by an order of magnitude than sap flow densities estimated for trees at the same site (ca. 2 9 10 -4 m 3 m -2 s -1 , Cech et al 2003). The missing root resistance in the potometer experiment probably only accounts for a small fraction of this large difference and ivy certainly has very high sap flow density.…”
Section: Discussionmentioning
confidence: 90%
“…Although light availability and quality (Ceulemans et al 1995), temperature and drying soils influence stomatal conductance in elevated CO 2 exposures, showed that changing vapour pressure deficit was the most important in explaining variation in both stomatal and canopy conductance in a FACE exposure in a closed canopy. Cech et al (2003) showed that reductions in sap flux density under elevated [CO 2 ], in a closed canopy free-air exposure, were greater during conditions of low evaporative demand (22%) and negligible (2%) during drier periods so that the magnitude of CO 2 effects depended on relative humidity. It is highly probable that leaf vapour pressure deficit, wind turbulence and temperature surrounding the leaf, and therefore the de-coupling co-efficient, differed in elevated compared with ambient Fig.…”
Section: Discussionmentioning
confidence: 98%